Hubungan Hukum Antara Perusahaan Properti dan Konsumen dalam Jual Beli Rumah Melalui Sistem Pre-Project Selling - Calvita; Ariawan Gunadi (CV Rewang Rencang, 2024)
In general, property companies in Indonesia utilize the pre-project selling system. However, this system often leads to legal issues, particularly for buyers, as it creates uncertainty and risks. One of the main reasons for these problems is that the objects being traded, whether houses or related facilities, are not yet available or completed at the time the transaction is conducted.This study employs a normative legal method with a regulatory and case study approach. The legal materials used include primary and secondary sources. The analysis is conducted qualitatively through deductive reasoning, and the results are presented descriptively. The findings indicate that the rights and obligations between parties in the pre-project selling system often rely on the principle of freedom of contract, as stipulated in Article 1338 of the Indonesian Civil Code. This provision includes exoneration clauses and grants significant protection to property companies. The official transfer of ownership rights can only occur after the issuance of the Deed of Sale and Purchase (Akta Jual Beli, or AJB) before a Land Deed Official (Pejabat Pembuat Akta Tanah, or PPAT). The study concludes that with the development of modern contract theories and consumer protection law, the primary focus is no longer solely on agreement and formal obligations but rather on ensuring fairness in providing information to consumers through the pre-project selling system. Property companies are prohibited from handing over the property or collecting more than 80% of payments from buyers if the Sale and Purchase Binding Agreement (Perjanjian Pengikatan Jual Beli, or PPJB) has not been executed. Furthermore, the PPJB must be drawn up before a notary to prevent future disputes.